2007
DOI: 10.1029/2007gl030283
|View full text |Cite
|
Sign up to set email alerts
|

Crustal uplift and sea level rise in northern Cascadia from GPS, absolute gravity, and tide gauge data

Abstract: [1] We combine data from nine GPS, absolute gravity, and tide gauge stations to estimate the relation between sea-level rise, vertical motion, and solid Earth processes in the Pacific Northwest. GPS vertical velocities (in ITRF2000) and absolute gravity rates are well correlated, with a gradient of 0.2 ± 0.1 mGal mm À1 , but show a significant offset of 0.53 ± 0.30 mGal yr À1 (2.2 ± 1.3 mm yr À1 ) (95% confidence). Tide gauge and GPS data indicate a northeast Pacific regional sea-level rise of 1.7 ± 0.5 mm yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 19 publications
8
49
0
Order By: Relevance
“…For the 1962 earthquake in Alaska, the ratio between coseismic gravity and height changes is closer to the Bouguer ratio than to the free-air gradient (BARNES, 1966). For the Cascadia subduction zone, MAZZOTTI et al (2007) found a ratio of -0.24 lGal mm -1 close to the predicted value of -0.19 lGal mm -1 from 10 years of continuous GPS and AG measurements. However, an offset between gravity and height variations is observed.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…For the 1962 earthquake in Alaska, the ratio between coseismic gravity and height changes is closer to the Bouguer ratio than to the free-air gradient (BARNES, 1966). For the Cascadia subduction zone, MAZZOTTI et al (2007) found a ratio of -0.24 lGal mm -1 close to the predicted value of -0.19 lGal mm -1 from 10 years of continuous GPS and AG measurements. However, an offset between gravity and height variations is observed.…”
Section: Introductionsupporting
confidence: 51%
“…This holds for all campaigns of applied geophysics because gravity has to be corrected for elevation changes in various ways (e.g., free air correction, Bouguer correction). In solid Earth geophysics, collocated gravity and position measurements are also strongly favored in studies dealing with postglacial rebound (PGR) (EKMAN and MÄ KINEN, 1996;LAMBERT et al, 2001LAMBERT et al, , 2006MÄ KINEN et al, 2007), tectonic motions (JACHENS, 1978;KARNER and WATTS, 1983;BALLU et al, 2003;TEFERLE et al, 2006;MAZZOTTI et al, 2007), coseismic deformation (BARNES, 1966;TANAKA et al, 2001;IMANISHI et al, 2004), volcanic activity (JOUSSET et al, 2000;FURUYA et al, 2003) or surface loading processes ZERBINI et al, 2004;NICOLAS et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, secular trends with approximately − 0.2, 0.9 and 0.5 μGal/year were detected at OMZ, KKG and TYH, respectively, for the whole observation periods. A similar unexplained positive long-term gravity trend of ~ 0.5 μGal/year is seen also in the Cascadia subduction zone (Mazzotti et al 2007).…”
Section: Discussionsupporting
confidence: 50%
“…However, only a small number of papers have reported inter-seismic gravity changes based on μGal-level precisions (Mazzotti et al 2007;Tanaka et al 2010;Van Camp et al 2011) (1 μGal = 10 −8 ms −2 ). Observed temporal gravity changes catch underground density redistributions, which can give us information that cannot be obtained from surface displacements.…”
Section: Introductionmentioning
confidence: 99%
“…This ratio is a function of the wavelength, the rheology and the history of the deformed layers and depends on the position of the load and on geodynamic process, so it depends on whether specific sites are located inside formerly glaciated areas, or peripheral, or in between; on how wide the respective ice sheet was, and whether there is elastic response due to contemporary ice changes, earthquakes or tectonic processes [Rundle, 1978;Wahr et [23] The ratio ( _ g/_ z) has not yet been experimentally determined with the required accuracy to allow discrimination between the modeled values [Ekman and Mäkinen, 1996;Lambert et al, 2001;Mazzotti et al, 2007]. For comparison, the observed gravity rates of change, converted into vertical velocities using the published plausible ratios are also shown in Figure 3b by the black (_ z observed = − _ g observed /1.0) and blue (_ z observed = − _ g observed /2.6) symbols, providing upper and lower values for the possible vertical velocities inferred from our AG measurements.…”
Section: Gravity Rates Of Change Versus Vertical Velocitiesmentioning
confidence: 99%